Selective RP-HPLC Determination of Pantoprazolein Pure and Pharmaceutical Dosage Forms - Gowri Sankar, D.; Raju, M.S.M.; Pawar, A.K.M. (Asian Journal of Chemistry, 2010)
A reverse phase high performance liquid chromatographic method has been developed for the estimation of pantoprazole in bulk and pharmaceutical formulations. The quantification was carried out using a techsphere silica column in isocratic mode, with mobile phase consisting of acetonitrile and water in the ratio of 60 : 40 (v/v). Beclomethasone dipropionate was used as an internal standard. The mobile phase was pumped at a rate of 1 mL/min and the detection was carried out at 289 nm. The linearity was found to be in the range of 3–15 μg/mL. The proposed method was found to be simple, precise, accurate, rapid and reproducible for the estimation of pantoprazole in pure and pharmaceutical dosage forms, i.e., tablets.